2013
DOI: 10.1177/1534650113496142
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated Mindfulness-Based Therapy for a Depressed College Student

Abstract: Mindfulness-based therapy (MBT) has shown promise in reducing depression and psychological distress among individuals presenting with various medical and psychiatric problems. This case study examined the implementation of MBT with an undergraduate student with recurrent major depression and generalized anxiety disorder. A novel four-session MBT protocol was utilized and the patient demonstrated significant decreases in depressive and anxiety symptoms and an overall increase in quality of life at the posttreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…Furthermore, deep breathing meditation aids in the reduction of physical symptoms of stress and anxiety exhibited in emotional disorders such as depression (Kabat-Zinn, 2003). A single case study by Preddy, McIndoo, and Hopko (2013) showed the reduction in depressive and anxious symptoms in a college student with major depression with mixed anxiety using short-term mindfulness-based treatment. There is also evidence that mindfulness can have interpersonal benefits in improving relational conflicts and relationship success (Davis & Hayes, 2011).…”
Section: Comorbid Anxietymentioning
confidence: 99%
“…Furthermore, deep breathing meditation aids in the reduction of physical symptoms of stress and anxiety exhibited in emotional disorders such as depression (Kabat-Zinn, 2003). A single case study by Preddy, McIndoo, and Hopko (2013) showed the reduction in depressive and anxious symptoms in a college student with major depression with mixed anxiety using short-term mindfulness-based treatment. There is also evidence that mindfulness can have interpersonal benefits in improving relational conflicts and relationship success (Davis & Hayes, 2011).…”
Section: Comorbid Anxietymentioning
confidence: 99%
“…However, when viewed from the balance of the instrument's contents, holistically, the measuring instrument has been able to explain individual problems' conditions and map the conditions of the measurement targets well (Fogaca, 2019;Klanecky et al, 2019;Reiland, 2017). The accuracy of the measurement results is also inseparable from the items' demographic diversity and condition by face validity, which is adjusted to the measuring instrument targets' characteristics (Li et al, 2008;Preddy et al, 2013).…”
Section: Figure 1 Test Information Function Dari Alat Ungkap Masalahmentioning
confidence: 99%
“…Changes or revisions to measuring students' problems should adjust to the characteristics of the measuring objectives themselves. Research that researched out in the last decade shows that there has been a change in generations' characteristics, especially concerning exposure to technology cross-cultural changes brought about by technology itself (Li et al, 2008;Preddy et al, 2013). The measuring instrument's target character for the condition of these psychological problems is often called the millennial generation; where the character is faster in mastering technology, is more likely to want simple literacy, is quick in making decisions so that he tends to dislike measuring instruments with many items (Fogaca, 2019;Klanecky, Ruhnke, & Meyer, 2019;Reiland, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan çalışmalar, bilinçli farkındalık temelli müdahelelerin özellikle kaygıyı ve kaygı semptomlarını (kalp çarpıntısı, terleme, titreme vb.) azaltmada büyük başarı elde ettiğini ortaya koymaktadır (Hofmann, Sawyer, Witt ve Oh, 2010;Preddy, McIndoo ve Hopko, 2013). Çünkü bilinçli farkındalık düzeyi yüksek olan bireylerin daha çok aktif stresle başa çıkma becerilerini kullandıkları ve stresli durumlardan daha az kaçarak onlarla daha fazla yüzleştikleri görülmektedir (Brown ve Ryan, 2003;Palmer ve Rodger, 2009).…”
Section: 2bilinçli Farkındalık Sınav Kaygısı Ve Dikkatunclassified